2018
DOI: 10.1063/1.5020905
|View full text |Cite
|
Sign up to set email alerts
|

Electric transport and the pseudogap in the 1-2-3 HTSC system, under all-around compression (Review Article)

Abstract: The problem of how high pressure impacts various electric transport mechanisms in HTSC compounds REBa2Cu3O7-δ (RE = Y, or another rare-earth ion) is considered. The features of the crystal structure and the effects that structural defects of different morphologies have on the electrical conductivity of these compounds in the normal, pseudogap, and superconducting states, are discussed. A review of the experimental data obtained in studies on the effect of high hydrostatic pressure on the various electric trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 166 publications
3
44
0
Order By: Relevance
“…Synthesis of novel superconducting materials with improved current-carrying abilities via modification of their structure and characteristics of electronic transport is one of the active research directions of modern solid state physics [1][2][3][4]. For high-temperature superconducting cuprates, the most efficient experimental approaches to accomplish this task include the introduction of artificial pinning sites [5][6][7] as well as the modification of their electronic transport properties via exposure to ionizing radiation [8,9] and variation of the composition [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of novel superconducting materials with improved current-carrying abilities via modification of their structure and characteristics of electronic transport is one of the active research directions of modern solid state physics [1][2][3][4]. For high-temperature superconducting cuprates, the most efficient experimental approaches to accomplish this task include the introduction of artificial pinning sites [5][6][7] as well as the modification of their electronic transport properties via exposure to ionizing radiation [8,9] and variation of the composition [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the use of these approaches can noticeably affect the temperature dependence of the conductivity of these compounds, thereby creating conditions for the observation of a series of intriguing phenomena occurring in the non-superconducting state. Exemplary phenomena include the pseudogap anomaly [1,2,37], fluctuation paraconductivity [38,39], metal-insulator transitions [40,41], incoherent electronic transport [42,43], making these studies especially important from the viewpoint of basic research [1]. According to the contemporary understanding [44], it is these phenomena which may be key to the clearing of the microscopic nature of hightemperature superconductivity, which remains unexplained despite almost 35 years of intensive experimental and theoretical investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the pseudogap (PG) anomaly remain one of the most topical research lines in the physics of high-temperature superconductivity (HTS). [1][2][3] However, in spite of the overwhelming literature (reviews can be found, e.g. in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…in Refs. [1][2][3][4][5], both the PG nature and its role in the formation of the superconducting state in HTSs remain unclear. In this regard, most promising are YBa 2 Cu 3 O 7−δ compounds 6,7 whose composition can be easily varied by substitution of Y for its isoelectronic analogues, 8,9 variation of the oxygen nonstoichiometry 10,11 or extreme exposures.…”
Section: Introductionmentioning
confidence: 99%